Symbols, Speech, and Electoral Influence: An Educational Sociolinguistic Study of Political Jargon in the 2024 Election - Aprilia, Fitria; Neisya; Azzahra, Siti Fatimah (Indonesian Research Journal in Education |IRJE|, 2024)
This study employs a qualitative and descriptive library research method to analyse viral political jargon circulating on social media, such as "AMIN," "Gemoy", "Sat Set - Tas Tes” and others. Data was collected using observation and note-taking techniques and analysed through a sociolinguistic framework to identify the forms, meanings, and factors contributing to the popularity of these expressions. The analysis process involved data reduction, data presentation, and conclusion drawing. Findings reveal that political jargon in this election includes words, phrases, clauses, and sentences, with morphological techniques like reduplication and affixation making the expressions memorable and relatable. These jargons carry denotative, connotative, and associative meanings, reflecting social and political values and enhancing political communication. This language use aids voters’ understanding and boosts public engagement in discourse. This research shows that political jargon serves as a communication tool to shape group identity and reinforce candidate narratives, providing insights into the intersections of language, politics, and culture in contemporary democracy.